Flotation reagent for high-sulfur lead zinc ore in low-alkali environment
In the low-alkali environment, the zinc activated combination pharmaceutical of the zinc sulfate and sulfate of sulfate or sulfulin ammonium ammonium ammonium ammonium ammonia in the low-alkali environment and the ethyl sulfonal amino acid-O-ester and n, n-two B, two second B The zinc catcher of sodium amino -alate -based amino -based aminophalate solves the problem of separation of iron Lightning ore and pyrite, and improves the taste and recovery rate of zinc in zinc concentrate.
Patent Information
- Application Number
- CN202411776625.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-01-21
Smart Images

Figure CN119327624A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lead-zinc ore flotation, and in particular to a flotation reagent for high-sulfur lead-zinc ore in a low-alkali environment. Background Art
[0002] As one of the strategic minerals, zinc is an important resource support for my country's new round of scientific and technological revolution and industrial transformation. Sphalerite in high-sulfur lead-zinc ore is one of the important mineral sources of zinc metal, and its activation and capture has always been a hot topic in the mineral processing industry at home and abroad. In high-sulfur lead-zinc ore, sphalerite and pyrite often coexist. In order to improve the grade of zinc in zinc concentrate, it is often necessary to suppress pyrite. At present, for the suppression of pyrite in high-sulfur lead-zinc ore, inhibitors in low-alkali environment are mostly used to replace the use of a large amount of lime.
[0003] However, the inventors discovered in the process of conceiving and realizing the present application that for the lead-zinc-iron flotation process of high-sulfur lead-zinc ore in a low-alkali environment, the efficient separation of sphalerite and pyrite in the lead tailings faces huge challenges. In the flotation recovery process of sphalerite, copper sulfate is usually used as an activator. However, as the iron content in sphalerite increases, the surface activation effect of copper sulfate on it weakens, resulting in poor floatability. When iron enters the sphalerite lattice in the form of isomorphism to replace zinc atoms, due to the differences in atomic electronic state density, energy band structure and steric hindrance, it is difficult for copper atoms to replace iron atoms on the sphalerite surface. Therefore, sphalerite exhibits the phenomenon of difficult activation and poor floatability. At the same time, copper sulfate has a strong activation effect on pyrite. When the amount of copper sulfate is increased to strengthen the activation of sphalerite, the floatability of pyrite in a low-alkali environment is easily increased, seriously affecting the efficient flotation separation of sphalerite and pyrite. This problem is more prominent when the pyrite content in the ore is high, that is, when the sulfur content in the lead-zinc ore increases, sphalerite and pyrite are more difficult to separate, and the zinc grade in the zinc concentrate obtained after the flotation separation of sphalerite and pyrite is lower. This shows that it is difficult to improve the zinc grade in the zinc concentrate using copper sulfate reagent alone as a zinc activator.
[0004] Therefore, in order to solve the problem of low zinc grade of zinc concentrate in the lead-zinc-iron flotation process of high-sulfur lead-zinc ore in a low-alkali environment, a flotation reagent for high-sulfur lead-zinc ore in a low-alkali environment is proposed.
[0005] The above contents are only used to assist in understanding the technical solution of the present invention and do not constitute an admission that the above contents are prior art. Summary of the invention
[0006] The main purpose of the present invention is to provide a flotation reagent for high-sulfur lead-zinc ore in a low-alkali environment, aiming to solve the problem of low zinc grade in the zinc concentrate obtained after flotation separation of sphalerite and pyrite in the lead-zinc-iron flotation process of high-sulfur lead-zinc ore.
[0007] To achieve the above object, the present invention provides a flotation reagent for high-sulfur lead-zinc ore in a low-alkali environment, the flotation reagent comprising a zinc activation combination reagent and a zinc collector, the zinc activation combination reagent consisting of copper sulfate and thioacetamide or ammonium dithiocarbamate, and the zinc collector consisting of ethylthiocarbamic acid-O-ester and sodium N,N-diethyldithiocarbamate.
[0008] Optionally, in the zinc activation combination agent, the mass ratio of copper sulfate to thioacetamide or ammonium dithiocarbamate is 1.5-3:1, and based on the mass of the original ore, the added amount of the zinc activation combination agent is 200-400 g / t.
[0009] Optionally, in the zinc collector, the mass ratio of ethylthiocarbamate-O-ester to sodium N,N-diethyldithiocarbamate is 1-2:1, and the amount of zinc collector added is 60-120 g / t based on the mass of the original ore.
[0010] In addition, to achieve the above purpose, the present invention also provides a flotation method for high-sulfur lead-zinc ore in a low-alkali environment, the method comprising:
[0011] S1, crush the high-sulfur lead-zinc ore and grind it to the target fineness -0.074mm 80%-90%;
[0012] S2, lead selection: after adding pH adjuster, sulfur inhibitor, zinc inhibitor, lead collector and frother to the grinding product in sequence, lead concentrate and lead selection tailings are obtained through lead roughing, lead scavenging and lead selection, wherein the lead selection tailings include sphalerite and pyrite;
[0013] S3, zinc selection: pH adjuster, sulfur inhibitor and the above-mentioned flotation reagent are sequentially added to the lead tailings, and finally a frother is added to obtain zinc concentrate and tailings through zinc roughing, zinc scavenging and zinc concentration, wherein the zinc activation combination reagent in the flotation reagent is added before the zinc collector.
[0014] Optionally, in S2 and S3, the sulfur inhibitor is a combination of sodium sulfite and sodium humate, and the mass ratio of the two is 97:3. Based on the mass of the original ore, the amount of sulfur inhibitor added in the lead roughing operation is 1000-2000g / t, and the amount added in the zinc roughing operation is 500-1000g / t.
[0015] Optionally, in S2, the zinc inhibitor is zinc sulfate, and based on the mass of the original ore, the amount of zinc sulfate added in the lead roughing operation is 800-2000g / t.
[0016] Optionally, in S2, the lead collector is at least one of butylamine black medicine and ethyl xanthate, and the amount of lead collector added in the lead roughing operation is 50-100 g / t based on the mass of the original ore.
[0017] Optionally, in S2 and S3, the foaming agent is at least one of pine oil and methyl isobutyl carbinol, and the added amount is 10-30 g / t based on the mass of the original ore.
[0018] Optionally, the iron content in the high-sulfur lead-zinc ore is 5%-25%, and the iron mainly exists in the form of pyrite.
[0019] Optionally, in S2 and S3, the pH adjuster is NaOH, and the pH of the slurry is adjusted to 9-9.5.
[0020] Principle of the invention:
[0021] Compared with copper sulfate, a single zinc activator, in the flotation reagent of the present invention, the zinc activation combination reagent can efficiently activate sphalerite, reduce the activation effect of copper ions on the surface of pyrite, improve the difference in surface hydrophilic and hydrophobic properties between sphalerite and pyrite, provide conditions for the selective adsorption of the zinc collector, and finally realize the effective separation of sphalerite and pyrite in a low-alkali environment, thereby improving the grade of zinc in the zinc concentrate.
[0022] The embodiment of the present invention provides a flotation reagent for high-sulfur lead-zinc ore in a low-alkali environment, which has at least the following beneficial effects:
[0023] 1. By adding a zinc activation combination agent of copper sulfate and thioacetamide or ammonium dithiocarbamate to the lead tailings, the synergistic effect of the zinc activation combination agents is utilized to enhance the activation of sphalerite by copper ions and reduce the activation of the surface of pyrite, thereby improving the separation rate of sphalerite and pyrite, reducing the content of pyrite, and improving the grade of zinc in the zinc concentrate;
[0024] 2. By adding a zinc collector composed of ethylthiocarbamate-O-ester and sodium N,N-diethyldithiocarbamate to the lead tailings, the selective collection ability of activated sphalerite is improved, and the recovery rate of zinc in the zinc concentrate is improved. At the same time, the problem that traditional collectors such as butyl xanthate cause pyrite to float strongly and enter the zinc concentrate is avoided, thereby improving the grade of zinc in the zinc concentrate;
[0025] 3. The zinc activation combination agent and zinc collector used in the new process are safe and non-corrosive to pipelines. They are often used in the production of catalysts, stabilizers, inhibitors, etc.
[0026] 4. In the lead-zinc-iron priority flotation process, the traditional process can be improved by replacing the conventional zinc activator copper sulfate and zinc collector without modifying the process facilities, which is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the process of the present invention.
[0028] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0029] In order to better understand the above technical solution, exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.
[0030] Based on the above description, an embodiment of the present invention is proposed as a flotation reagent for high-sulfur lead-zinc ore in a low-alkali environment.
[0031] First embodiment
[0032] The Pb grade of a high-sulfur lead-zinc sulfide ore is 6.23%, the Zn grade is 18.28%, and the Fe grade is 16.84%. The specific flotation process includes the following steps:
[0033] 1) The raw ore is crushed and ground, and the -0.074 mm particle size accounts for 80% of the ground product;
[0034] 2) adding NaOH to the grinding product obtained in step 1) to adjust the pH value of the pulp to 9.0, and then sequentially adding 1500 g / t of sulfur inhibitor, 2000 g / t of zinc inhibitor, 100 g / t of butylamine black medicine, and 30 g / t of pine oil, and obtaining lead concentrate and lead tailings after one roughing selection, two scavenging selections, and three concentrating selections;
[0035] 3) To the lead tailings obtained in step 2), NaOH was added to adjust the pH of the slurry to 9.0, and then 750 g / t of sulfur inhibitor, 400 g / t of zinc activator (copper sulfate and thioacetamide in a mass ratio of 1.5:1), 120 g / t of zinc collector (ethyl thiocarbamate-O-ester and sodium N,N-diethyldithiocarbamate in a mass ratio of 1:1), and 30 g / t of pine oil were added in sequence, and zinc concentrate and tailings were obtained through one roughing, two scavenging and three concentrating. The test results are shown in Table 1.
[0036] Table 1 Flotation test results / %
[0037]
[0038] It can be seen from the table that the zinc grade in the obtained zinc concentrate is 53.84%, the iron grade is 4.74%, and the zinc recovery rate is 90.36%.
[0039] Second embodiment
[0040] The Pb grade of a high-sulfur lead-zinc sulfide ore is 4.16%, the Zn grade is 12.54%, and the Fe grade is 19.87%. The specific flotation process includes the following steps:
[0041] 1) The raw ore is crushed and ground, and the -0.074 mm particle size accounts for 85% of the ground product;
[0042] 2) adding NaOH to the ground product obtained in step 1) to adjust the pH value of the pulp to 9.5, and then sequentially adding 2000 g / t of sulfur inhibitor, 1500 g / t of zinc inhibitor, 80 g / t of butylamine black medicine, and 20 g / t of pine oil, and obtaining lead concentrate and lead tailings after one roughing selection, two scavenging selections, and three cleaning selections;
[0043] 3) To the lead tailings obtained in step 2), NaOH was added to adjust the pH of the slurry to 9.5, and then 1000 g / t of sulfur inhibitor, 300 g / t of zinc activator (copper sulfate and ammonium dithiocarbamate in a mass ratio of 3:1), 90 g / t of zinc collector (ethylthiocarbamate-O-ester and sodium N,N-diethyldithiocarbamate in a mass ratio of 2:1), and 20 g / t of pine oil were added in sequence. Zinc concentrate and tailings were obtained through one roughing, two scavenging and three concentrating. The test results are shown in Table 2.
[0044] Table 2 Flotation test results / %
[0045]
[0046] It can be seen from the table that the zinc grade in the obtained zinc concentrate is 52.76%, the iron grade is 5.93%, and the zinc recovery rate is 91.17%.
[0047] Third embodiment
[0048] The Pb grade of a high-sulfur lead-zinc sulfide ore is 2.47%, the Zn grade is 7.62%, and the Fe grade is 9.81%. The specific flotation process includes the following steps:
[0049] 1) The raw ore is crushed and ground, and the -0.074mm particle size accounts for 90% of the ground product;
[0050] 2) adding NaOH to the ground product obtained in step 1) to adjust the pH value of the slurry to 9.0, and then sequentially adding 1000 g / t of sulfur inhibitor, 800 g / t of zinc inhibitor, 50 g / t of ethyl xanthate, and 10 g / t of methyl isobutyl carbinol, and obtaining lead concentrate and lead tailings after one roughing selection, two scavenging selections, and three cleaning selections;
[0051] 3) To the lead tailings obtained in step 2), NaOH was added to adjust the slurry pH to 9.0, and then 500 g / t of sulfur inhibitor, 200 g / t of zinc activator (copper sulfate and ammonium dithiocarbamate in a mass ratio of 2:1), 60 g / t of zinc collector (ethylthiocarbamate-O-ester and sodium N,N-diethyldithiocarbamate in a mass ratio of 1.5:1), and 20 g / t of pine oil were added in sequence. Zinc concentrate and tailings were obtained through one roughing, two scavenging and three concentrating. The test results are shown in Table 3.
[0052] Table 3 Flotation test results / %
[0053]
[0054] It can be seen from the table that the zinc grade in the obtained zinc concentrate is 52.61%, the iron grade is 4.39%, and the zinc recovery rate is 91.20%.
[0055] The first comparison
[0056] The other conditions are the same as those in Example 1, except that copper sulfate is used as the zinc activator and butyl xanthate is used as the zinc collector. The test results are shown in Table 4.
[0057] Table 4 Flotation test results / %
[0058]
[0059] It can be seen from the table that the zinc grade in the obtained zinc concentrate is 46.11%, the iron grade is 10.87%, and the zinc recovery rate is 88.90%. Compared with the test results of Example 1, the Zn grade in the zinc concentrate is significantly reduced, the Fe content is greatly increased, the separation effect of sphalerite and pyrite is worse than that of Example 1, and the Zn recovery rate is reduced.
[0060] The second comparison
[0061] The other conditions are consistent with those in Example 1, except that only copper sulfate is used as the zinc activator. The test results are shown in Table 5.
[0062] Table 5 Flotation test results / %
[0063]
[0064]
[0065] As can be seen from the table, the zinc grade in the obtained zinc concentrate is 51.41%, the iron grade is 6.89%, and the zinc recovery rate is 81.18%. Compared with the test results of Example 1, the Zn recovery rate in the zinc concentrate is greatly reduced, and the recovery of marmatite is worse than that of Example 1, indicating that the zinc combination activator has a stronger activation effect on marmatite than single copper sulfate.
[0066] The third comparison
[0067] The other conditions are the same as those in Example 1, except that butyl xanthate is used as the zinc collector. The test results are shown in Table 6.
[0068] Table 6 Flotation test results / %
[0069]
[0070] It can be seen from the table that the zinc grade in the obtained zinc concentrate is 47.53%, the iron grade is 8.92%, and the zinc recovery rate is 90.39%. Compared with the test results of Example 1, the Zn grade in the zinc concentrate is reduced, the Fe content is increased, and the separation effect of sphalerite and pyrite is worse than that of Example 1, indicating that the zinc collector has stronger selectivity than butyl xanthate.
[0071] The fourth comparison
[0072] Other conditions are consistent with those in Example 2, except that only copper sulfate is used as the zinc activator. The test results are shown in Table 7.
[0073] Table 7 Flotation test results / %
[0074]
[0075]
[0076] As can be seen from the table, the zinc grade in the obtained zinc concentrate is 50.74%, the iron grade is 7.69%, and the zinc recovery rate is 80.39%. Compared with the test results of Example 2, the Zn recovery rate in the zinc concentrate is greatly reduced, and the recovery of marmatite is worse than that of Example 2, indicating that the zinc combination activator has a stronger activation effect on marmatite than single copper sulfate.
[0077] Fifth comparison
[0078] The other conditions are consistent with those in Example 2, except that butyl xanthate is used as the zinc collector. The test results are shown in Table 8.
[0079] Table 8 Flotation test results / %
[0080]
[0081] It can be seen from the table that the zinc grade in the obtained zinc concentrate is 47.54%, the iron grade is 9.87%, and the zinc recovery rate is 88.25%. Compared with the test results of Example 2, the Zn grade in the zinc concentrate is reduced, the Fe content is increased, and the separation effect of sphalerite and pyrite is worse than that of Example 2, indicating that the zinc collector has stronger selectivity than butyl xanthate.
[0082] Sixth comparison
[0083] Other conditions are consistent with those in Example 3, except that only copper sulfate is used as the zinc activator. The test results are shown in Table 9.
[0084] Table 9 Flotation test results / %
[0085]
[0086]
[0087] As can be seen from the table, the zinc grade in the obtained zinc concentrate is 50.96%, the iron grade is 6.21%, and the zinc recovery rate is 79.46%. Compared with the test results of Example 3, the Zn recovery rate in the zinc concentrate is greatly reduced, and the recovery of marmatite is worse than that of Example 3, indicating that the zinc combination activator has a stronger activation effect on marmatite than single copper sulfate.
[0088] Seventh comparison
[0089] The other conditions are consistent with those in Example 3, except that butyl xanthate is used as the zinc collector. The test results are shown in Table 10.
[0090] Table 10 Flotation test results / %
[0091]
[0092] It can be seen from the table that the zinc grade in the obtained zinc concentrate is 48.12%, the iron grade is 7.93%, and the zinc recovery rate is 91.49%. Compared with the test results of Example 3, the Zn grade in the zinc concentrate is reduced, the Fe content is increased, and the separation effect of sphalerite and pyrite is worse than that of Example 3, indicating that the zinc collector has stronger selectivity than butyl xanthate.
[0093] In summary, when processing high-sulfur lead-zinc ore, when only copper sulfate is used as the activator of marmatite, the zinc recovery rate in the zinc concentrate is low, and the marmatite cannot be efficiently flotated and recovered; when the conventional collector butyl xanthate is used as the zinc collector, a large amount of pyrite floats up during the flotation of marmatite, the pyrite content in the zinc concentrate increases, and the quality of the zinc concentrate is significantly reduced; using a combination of copper sulfate and thioacetamide or ammonium dithiocarbamate as a zinc combination activator, and a combination of ethylthiocarbamate-O-ester and sodium N,N-diethyldithiocarbamate as a zinc collector, it is possible to achieve efficient activation of marmatite and its precise separation from pyrite, thereby improving the grade of zinc in the zinc concentrate and the recovery rate of zinc.
[0094] It should be noted that, although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0095] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A flotation reagent for high-sulfur lead-zinc ore in a low-alkali environment, characterized in that: The flotation reagent comprises a zinc activation combination reagent and a zinc collector, wherein the zinc activation combination reagent is composed of copper sulfate and thioacetamide or ammonium dithiocarbamate, and the zinc collector is composed of ethyl thiocarbamic acid-O-ester and sodium N,N-diethyl dithiocarbamate.
2. The flotation reagent according to claim 1, characterized in that In the zinc activation combination agent, the mass ratio of copper sulfate to thioacetamide or ammonium dithiocarbamate is 1.5-3:
1. Based on the mass of the original ore, the addition amount of the zinc activation combination agent is 200-400g / t.
3. The flotation reagent according to claim 1, characterized in that In the zinc collector, the mass ratio of ethylthiocarbamate-O-ester to sodium N,N-diethyldithiocarbamate is 1-2:1, and the added amount of the zinc collector is 60-120 g / t based on the mass of the original ore.
4. A flotation method for high-sulfur lead-zinc ore in a low-alkali environment, characterized in that: The method comprises: S1, crush the high-sulfur lead-zinc ore and grind it to the target fineness -0.074mm 80%-90%; S2, lead selection: after adding pH adjuster, sulfur inhibitor, zinc inhibitor, lead collector and frother to the grinding product in sequence, lead concentrate and lead tailings are obtained through lead roughing, lead scavenging and lead concentration; S3, zinc optimization: add pH adjuster, sulfur inhibitor and flotation reagent as claimed in claim 1 to the lead tailings in sequence, and finally add frother, and obtain zinc concentrate and tailings through zinc roughing, zinc scavenging and zinc concentration, wherein the zinc activation combination agent in the flotation reagent is added before the zinc collector.
5. The method according to claim 4, characterized in that In S2 and S3, the sulfur inhibitor is a combination of sodium sulfite and sodium humate, and the mass ratio of the two is 97:
3. Based on the mass of the original ore, the amount of the sulfur inhibitor added in the lead roughing operation is 1000-2000g / t, and the amount added in the zinc roughing operation is 500-1000g / t.
6. The method according to claim 4, characterized in that In the S2, the zinc inhibitor is zinc sulfate. Based on the mass of the original ore, the amount of zinc sulfate added in the lead roughing operation is 800-2000g / t.
7. The method according to claim 4, characterized in that In S2, the lead collector is at least one of butylamine black medicine and ethyl xanthate. Based on the mass of the original ore, the amount of lead collector added in the lead roughing operation is 50-100g / t.
8. The method according to claim 4, characterized in that In S2 and S3, the foaming agent is at least one of pine oil and methyl isobutyl carbinol, and the added amount is 10-30 g / t based on the mass of the original ore.
9. The method according to claim 4, characterized in that The iron content in the high-sulfur lead-zinc ore is 5%-25%.
10. The method according to claim 4, characterized in that In S2 and S3, the pH adjuster is NaOH, which is used to adjust the pH of the slurry to 9-9.5.
Citation Information
Patent Citations
Physical concentration and phosphorus reduction method for skarn-type high-phosphorus molybdenum ore
CN105381868A
Flotation method with lead-sulfur-zinc sequential priority
CN108372030A
Beneficiation method of high-sulfur lead zinc ores under high-temperature environment
CN109174459A
Beneficiation method for high-sulfur lead-zinc ore
CN111715411A
High-sulfur lead-zinc ore beneficiation method under natural pH condition
CN113731642A
Cited By
Zinc collecting agent GZ-1 and preparation method and application thereof
CN119793704A